Effect of Rice Husk Ash and Clay Powder as Cooling Media in Post Weld Heat Treatment (PWHT) on The Impact Toughness of SMAW-Welded SS400 Steel - Angga Hermawansyah; Zainal Abadi; Delima Yanti Sari; Rifelino (Unversitas Negeri Padang, 2026)
This study investigates the effect of variations in cooling media during Post Weld Heat Treatment (PWHT) on the impact toughness of low carbon steel SS400. The main problem addressed in this research is how differences in cooling medium characteristics influence the cooling rate, which subsequently affects the impact toughness of welded material. The objective of this study is to determine the effect of using rice husk ash, clay, and air as cooling media on the impact toughness value of SS400 steel. The experimental method was employed by applying PWHT to SMAW-welded specimens, followed by Charpy impact testing to obtain the final deflection angle, which was then converted into impact energy and impact value (HI). The results show that clay cooling medium provides the highest average impact toughness value of 1.175 J/mm², followed by rice husk ash at 1.107 J/mm², while air cooling yields the lowest value of 0.845 J/mm². These differences indicate that the thermal characteristics of the cooling media significantly influence the material’s ability to absorb energy before fracture, which is related to the stability of the cooling rate during the PWHT process. It can be concluded that variations in cooling media affect the impact toughness of SS400 steel, where more stable cooling conditions lead to higher toughness values.